Live wild animal exports to supply the exotic pet trade: A case study from Togo using publicly available social media data - Lauren A. Harrington; Mark Auliya; Harry Eckman; Alix P. Harrington; David W. Macdonald; Neil D'Cruze (Conservation Science and Practice, 2021)
Abstract Exotic pet supply is a key, predominantly legal, component of global wildlife trade, but few studies have quantified its diversity or global reach. Here, using information extracted from the public (open) Facebook accounts of two wildlife exporters in Togo, West Africa, we identified at least 200 species, predominantly reptiles, but also mammals, birds, amphibians and invertebrates, advertised as available for sale and export, between the years 2016 and 2020. Of the animals identified, several hundred, possibly several thousand, individuals were shipped, at least monthly, to North America, Europe, Asia, and elsewhere in Africa, via a number of major airlines. Among the vertebrates observed, approximately one‐third had not yet been evaluated on the IUCN Red list, and three quarters were not CITES‐listed (i.e., their trade was not regulated under this international treaty). The apparent lack of adequate monitoring of population status, disease, biological invasion, and animal welfare risks associated with this trade, as well as neglected taxa (e.g., invertebrates), has potential implications for environmental, public, and animal health. The findings of this case study suggest that a systematic review of social media activity could efficiently reveal significant insights into the otherwise undocumented global supply of exotic pets, directing legislators to aspects and areas where regulation is insufficient, and informing international and national policy change.